Types and concentrations of cytokinins in the micropropagation of Anthurium maricense - Cecília Moreira Serafim; Arlene Santisteban Campos; Priscila Bezerra dos Santos Melo; Ana Cecília Ribeiro de Castro; Ana Cristina Portugal Pinto de Carvalho (Agro@mbiente On-line, 2018)
Faced with the demand for plants potted for their foliage, Anthurium maricense is seen as a viable option. However, most of the studies on obtaining micropropagated plantlets are for A. andraeanum, with nothing yet reported for A. maricense. The aim of this study therefore, was to evaluate the effect of four cytokinins in different concentrations, on the in vitro induction of shoots from nodal segments of A. maricense. The experimental design was completely randomised in a 4 x 4 factorial scheme, with four cytokinins (BAP, ZEA, CIN and 2iP) and 4 concentrations (0, 2.22, 4.44 and 6.66 μM), for a total of 16 treatments, with 6 replications of five test tubes, and using one nodal segment. Cultures were kept in a growth room at 25 ± 2°C, a photoperiod of 16 h and a light intensity of 30 μmolm-2 s-1 for 60 days. After this period, the number of shoots formed per node was evaluated. The addition of a cytokinin to the culture medium was determinant for the in vitro regeneration of shoots in A. maricense. The greatest estimated number of shoot formations in A. maricense were obtained in the culture media containing ZEA (3.87) and BAP (3.30), both at concentration of 6.66 μM.